Observations of out-of-pocket travel costs in seeking free cardiac care in India: would point-of-care ultrasound help? - Camryn J. Kimura; Keshav R. Nayak; Reeta Varyani; Prayaag Kini; Jill Waalen; Bruce J. Kimura (BMC Health Services Research, 2024)
Abstract Background In consideration of patient out-of-pocket costs in low- and middle-income countries, this observational cohort study sought to quantify the travel expenses associated with receiving free cardiac services in India and create a point-of-care ultrasound (POCUS) referral model. Methods In a tertiary hospital that offers free services in Bangalore, India, we interviewed outpatients awaiting cardiac evaluation regarding their out-of-pocket expenses. A subgroup underwent POCUS for signs of left atrial enlargement, inferior vena cava plethora, and extravascular lung water, and subsequent chart review for significant findings on echocardiography or need for immediate care. A model was tested in which a normal POCUS would negate the requirement for referral. Results Patients (N = 219), of age (mean ± SD) 49.0 ± 12.9 y, traveled [median (IQR)] 1178 miles (248–1240), spent $104 ($26-$195), and lost 4.5 (0–10) days of work at a daily wage of $3.90 ($1.95-$6.50). The one-way travel cost equated to 27 days of daily pay. In the POCUS subgroup, symptoms were commonly chest pain (57%) and dyspnea (48%) and were less than moderate in severity (71%). Abnormal echo findings were present in 54% of patients, of whom 29% needed immediate care, and 71% were dismissed without follow-up. POCUS signs were related to an abnormal echo (p < 0.001), but not immediate care (p = 0.50). POCUS-based referral would have prevented 51% (35/68) of unnecessary referrals and missed 13% (9/68) of cases that required immediate care. Conclusions Out-of-pocket costs, relative to income, can be significant for those seeking free cardiac care. POCUS performed locally could potentially reduce the costs of travel but would risk missing cases, depending on symptom type.